An analysis of cooperation networks related to research projects between universities in the Chungcheong region in Korea: Suggestions for strengthening university networks - Choi, Young-Chool; Jang, Ji-Hyun (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective: The aim of this study is to obtain information regarding how 54 universities in the Chungcheong region of Korea are conducting joint research among themselves. More specifically, the study aims to understand the network characteristics and main patterns according to which universities in the Chungcheong region are conducting joint research, and to obtain the information necessary to utilize the network structure between universities as a strategy for future regional development. Design/Meghodology/Appraoch: For this purpose, we investigated the number of joint research projects conducted among these 54 universities in 2022, thereby obtaining the most up-to-date information possible. Network analysis was performed based on the surveyed data. Result/Discussion: The research results show that a total of five clusters exist in the Chungcheong area. The universities that play a central role include KAIST, Chungnam National University, Chungbuk National University, Kongju University and Korea National University of Transportation. Conclusions: Because these universities constitute important bases in the region and have close links with neighbouring universities, they are expected to play an important role in future regional development. Originality/Value: One of the academic implications of this study is that it applied social network analysis methods to research-related partnerships between universities in the Chungcheong region to identify universities that play an important key role.